2022
DOI: 10.1186/s40068-022-00254-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of DPSIR model to identify the drivers and impacts of land use and land cover changes and climate change on land, water, and livelihoods in the L. Kyoga basin: implications for sustainable management

Abstract: Land use, land cover, and climate change impacts are current global challenges that are affecting many sectors, like agricultural production, socio-economic development, water quality, and causing land fragmentation. In developing countries like Uganda, rural areas with high populations dependent on agriculture are the most affected. The development of sustainable management measures requires proper identification of drivers and impacts on the environment and livelihoods of the affected communities. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 75 publications
1
2
0
2
Order By: Relevance
“…Wondim, Mosa, and Alehegn 2016; Dersseh et al 2020; Enyew, Assefa, and Gezie 2020; Ayele and Atlabachew 2021b; Damtie, Mengistu, and Meshesha 2021; Dersseh et al 2022), who studied three shallow bays along the Lake Tana shoreline and reported the highest eutrophication in the agriculture-impacted bays due to invasion of the wetlands and inshore lake by water hyacinth. The ndings also agree with studies carried out in other African Lakes, for example, in the Lake Kyoga basin of Uganda byObubu et al (2022), Lake Victoria of Kenya byOtieno et al (2022), in Lake Victoria of Uganda byWanda et al (2015), and in the African Great Lakes(Plisnier et al 2022). …”
supporting
confidence: 90%
“…Wondim, Mosa, and Alehegn 2016; Dersseh et al 2020; Enyew, Assefa, and Gezie 2020; Ayele and Atlabachew 2021b; Damtie, Mengistu, and Meshesha 2021; Dersseh et al 2022), who studied three shallow bays along the Lake Tana shoreline and reported the highest eutrophication in the agriculture-impacted bays due to invasion of the wetlands and inshore lake by water hyacinth. The ndings also agree with studies carried out in other African Lakes, for example, in the Lake Kyoga basin of Uganda byObubu et al (2022), Lake Victoria of Kenya byOtieno et al (2022), in Lake Victoria of Uganda byWanda et al (2015), and in the African Great Lakes(Plisnier et al 2022). …”
supporting
confidence: 90%
“…In Nigeria, the driving forces of LULC changes include agricultural expansion, livestock production systems, artisanal shing, agricultural production and capacity development constraints, livelihood status and options, and institutional and policy support. These activities have led to converting natural areas into built-up areas and agricultural land, with potential impacts such as habitat loss, reduced biodiversity, and increased soil erosion [55], [56].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to increase the efforts to study DCh in unprotected areas, where they could be occurring more frequently. It is important to consider that a systematic search for specialized literature (as the one conducted in this research) is an auxiliary tool to identify DCh; there are other direct methods or tools to estimate these (como la utilizada en esta investigación) constituye una herramienta auxiliar para la identificación de IC; existen otros métodos o herramientas directas para contabilizar de estos impactos, tales como las entrevistas (Shalizi et al, 2020), uso de imágenes satelitales (Lahai et al, 2022) y anotaciones observacionales (Obubu et al, 2022). Estas estrategias pueden ser utilizadas en especial para aquellos humedales menos estudiados.…”
Section: Discussionunclassified
“…Esto último nos permite insistir en la necesidad de un adecuado planeamiento territorial. Los humedales costeros generalmente se encuentran rodeados por urbanizaciones que, en muchos casos, generan la alteración en la sedimentación y la dinámica de nutrientes (Faulkner, 2004); además de causar efectos negativos sobre el régimen hidrológico y de relacionarse con la deposición de los contaminantes químicos por el mal manejo de las aguas residuales (Rodríguez et al, 2017; Camas-Guardamino impacts, such as interviews (Shalizi et al, 2020), satellite images (Lahai et al, 2022), and observational notes (Obubu et al, 2022).…”
Section: Discussionunclassified